Sharia Restricted Intermediary Account (SRIA) Dalam Pengembangan Keuangan Syariah di Indonesia - Solikhah, Lailatus; Mochammad Andre Agustianto (Jurnal Investasi Islam, 2024)
This study aims to explore the concept, scheme, regulation, and challenges faced by Sharia Restricted Intermediary Account (SRIA) in the development of Islamic finance in Indonesia. SRIA, which uses the Mudharabah Muqayyadah contract, is an innovative investment product in Islamic banking designed to meet the needs of the community for investments that are in accordance with Islamic principles. This study uses a qualitative descriptive approach with a literature study method to analyze data relevant to Sharia Restricted Intermediary Account (SRIA). The results of the study indicate that SRIA has characteristics that distinguish it from conventional banking products and other Islamic investment instruments and has received observations from the Financial Services Authority and the National Committee for Islamic Finance to ensure the suitability of the scheme to Islamic aspects. In addition, this study identifies factors that encourage individuals to invest by choosing Islamic products, such as improving the quality of life in the future, reducing the impact of inflation, and tax efficiency. This study also compares SRIA with other Islamic investment instruments such as Sukuk, Islamic stocks, and Islamic mutual funds. Based on the comparison, sharia investment instruments have similarities and differences, so investors must be able to consider investment decisions with sharia financial instruments that suit their needs and abilities. Thus, SRIA is expected to be a safer and more controlled investment alternative for investors, as well as provide a significant contribution to the growth of the sharia financial sector in Indonesia.